X-ray densitometry investigation of bone mineral density in women: Regional aspects - G. I. Kolpinskiy; I. S. Zakharov (Вестник рентгенологии и радиологии)
Objective: to calculate Z scores for different age groups of women in the Kemerovo region, by relying on the developed database for two-dimensional bone mineral densities (BMD) of the lumbar vertebra and proximal femoral bone.Material and methods. This given investigation analyzed 1504 results of dual-energy X-ray absorptiometry of the lumbar vertebra and proximal femoral bone in healthy  women from the Kemerovo Region.Results. The performed investigation revealed that the peak bone mass of the lumbar spine and proximal femoral bone in the Kuzbass women corresponded to that of 20–29-year olds. In the women of the Kemerovo Region, the population-based lumbar vertebral BMDs significantly differed from those available in the NHANES III database starting from 30 years of age. Thus, the developed BMD database has regional features and must be used to calculate a Z score for the female population of Kuzbass. By taking into account the fact that were no differences in the peak body mass values of the women in the two compared groups in accordance of the guidelines of the International Society for Clinical  ensitometry; the NHANES III database may be used to estimate a T score.